Macroeconomics of international price discrimination - Giancarlo Corsetti; Luca Dedola (European Central Bank (ECB), 2002)
This paper builds a baseline two-country model of real and monetary transmission under optimal international proce discrimination. Distributing traded goods to consumers reuires nontradables; because of distributive trade, the proce elasticity of export demand depends on the exchange rate. Profit-maximizing monopolistic firms drive a wedge between wholesale and retial proces across countries. This entails possibly large deviations from the law of one price and incomplete pass-through on import prices. Yet, consistent with expenditure-switching effects, a nominal repreciation generally worsens the terms of trade. Moreover, the exchange rate and the terms of trade can be more volatile than fundamentals. For plausible ranges of the distribution margin, there can be multiple steady states, whereas large differences in nominal and real exhange rates across equilibria translate into small differences in consumption, employment and the price level. Finally, we show that with competitive goods markets international policy cooperation is redundant even under financial autarky.
Keywords: F3; F4; 330; Exchange Rate Pass-Through; international cooperation; nominal rigidities; optimal cyclical monetary policy; wholesale and retail services